2006
DOI: 10.1051/0004-6361:20054551
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of multiple protoplanets embedded in a protostellar disc

Abstract: Context. Theory predicts that low mass protoplanets in a laminar protostellar disc will migrate into the central star prior to disc dispersal. It is known that protoplanets on orbits with eccentricity e > ∼ H/r, where H is the disc scale height and r is the radius, can halt or reverse their migration. Aims. We examine whether a system of interacting protoplanetary cores can excite and sustain significant eccentricity of the population, allowing some planetary cores to survive in the disc over its lifetime. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
232
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(254 citation statements)
references
References 47 publications
(69 reference statements)
22
232
0
Order By: Relevance
“…Papaloizou & Larwood (2000) have also considered larger values for e and they find an extended eccentricity damping timescale such that de/dt ∝ e −2 if e > 1.1H/r. Cresswell & Nelson (2006) have performed hydrodynamical simulations of embedded small mass planets and find good agreement with the work by Papaloizou & Larwood (2000). These 2D results have been confirmed by Cresswell et al (2007) using fully 3D isothermal simulations.…”
Section: Introductionsupporting
confidence: 75%
“…Papaloizou & Larwood (2000) have also considered larger values for e and they find an extended eccentricity damping timescale such that de/dt ∝ e −2 if e > 1.1H/r. Cresswell & Nelson (2006) have performed hydrodynamical simulations of embedded small mass planets and find good agreement with the work by Papaloizou & Larwood (2000). These 2D results have been confirmed by Cresswell et al (2007) using fully 3D isothermal simulations.…”
Section: Introductionsupporting
confidence: 75%
“…HD 128311, a two-planet system, also appears to carry a signature of similar scattering (Sándor & Kley 2006 the required disk behavior and that predicted by hydrodynamical theories (Kley et al 2004). Simulations that include multiple protoplanets interacting with a protoplanet swarm show that most protoplanets will eventually accrete on to the star, leading to a planet occurrence rate lower than that observed (Cresswell & Nelson 2006). The increasing number of characterized multiplanet systems should help constrain these theories.…”
Section: Multiple-planet Systems and Planet Formation Theorymentioning
confidence: 75%
“…Second, the method of implementing in a N-body calculation synthetic forces computed from a 1D disk model is qualitatively reliable. It has been widely tested and used in similar studies, where it was shown to mimic the important gas effects on planets observed in genuine hydrodynamical simulations (e.g., Cresswell & Nelson 2006Morbidelli et al 2008).…”
Section: Methodsmentioning
confidence: 99%